SEAPOP studies in the Barents and Norwegian Seas in 2007 - Anker-Nilssen, Tycho; Barrett, Robert T.; Bustnes, J.O.; Christensen-Dalsgaard, Signe; Erikstad, K.E.; Fauchald, Per; Lorentsen, Svein-Håkon; Steen, Harald; Strøm, H.; Systad, Geir Helge; Tveraa, Torkild (Norsk institutt for naturforskning, 2008)
This is the third annual report of the SEAPOP programme, which was initiated in 2005. In 2007, the work continued at full scale in the Lofoten-Barents Sea area, and similar studies were initiated in the southern part of the Norwegian Sea. The report is divided into three sections. The first is an executive summary, the second presents five selected highlights from the studies in 2007, whereas the third presents results from other projects within the programme. The programme is wide-ranging and with at least 17 project activities running in parallel, there is no room for details of the results in this short abstract. The main effort is however being put into mapping and monitoring. The most demanding activity is to build-up the long-term data series for the numerical development, reproduction, survival and diet of an ecological and geographical selection of breeding populations. This is made at a series of key-sites, no numbering nine locations after the inclusion of two new sites in central Norway (Sklinna and Runde) in 2007. Comparative analyses of these data series, across species and sites and against various environmental factors, are essential for explaining any documented changes and to predict future population trends. SEAPOP also aims to take advantage of advances in technology and develop more efficient methods of data collection, and uses high-tech data sampling techniques to document migration patterns and habitat use in species of special conservation concern. Seabirds are mapped both along the coast and at sea. To balance resource use against minimum requirements for validity of data, coastal areas are covered such that each area is mapped once every ten years in each season (breeding, moulting/autumn, winter and spring). The distribution and abundance of seabirds at sea in the various seasons are modelled from documented associations between oceanographic factors and the distribution of different seabird species and their prey. These associations are derived from data collected in a ...